Use of chitin and chitosan to produce new chitooligosaccharides by chitinase Chit42: enzymatic activity and structural basis of protein specificity - Kidibule, Peter Elias (Microb Cell Fact, 2018)
BACKGROUND: Chitinases are ubiquitous enzymes that have gained a recent biotechnological attention due to their ability to transform biological waste from chitin into valued chito-oligomers with wide agricultural, industrial or medical applications. The biological activity of these molecules is related to their size and acetylation degree. Chitinase Chit42 from Trichoderma harzianum hydrolyses chitin oligomers with a minimal of three N-acetyl-d-glucosamine (GlcNAc) units. Gene chit42 was previously characterized, and according to its sequence, the encoded protein included in the structural Glycoside Hydrolase family GH18. RESULTS: Chit42 was expressed in Pichia pastoris using fed-batch fermentation to about 3 g/L. Protein heterologously expressed showed similar biochemical properties to those expressed by the natural producer (42 kDa, optima pH 5.5–6.5 and 30–40 °C). In addition to hydrolyse colloidal chitin, this enzyme released reducing sugars from commercial chitosan of different sizes and acetylation degrees. Chit42 hydrolysed colloidal chitin at least 10-times more efficiently (defined by the k(cat)/K(m) ratio) than any of the assayed chitosan. Production of partially acetylated chitooligosaccharides was confirmed in reaction mixtures using HPAEC-PAD chromatography and mass spectrometry. Masses corresponding to (d-glucosamine)(1–8)-GlcNAc were identified from the hydrolysis of different substrates. Crystals from Chit42 were grown and the 3D structure determined at 1.8 Å resolution, showing the expected folding described for other GH18 chitinases, and a characteristic groove shaped substrate-binding site, able to accommodate at least six sugar units. Detailed structural analysis allows depicting the features of the Chit42 specificity, and explains the chemical nature of the partially acetylated molecules obtained from analysed substrates. CONCLUSIONS: Chitinase Chit42 was expressed in a heterologous system to levels never before achieved. The enzyme produced small partially acetylated chitooligosaccharides, which have enormous biotechnological potential in medicine and food. Chit42 3D structure was characterized and analysed. Production and understanding of how the enzymes generating bioactive chito-oligomers work is essential for their biotechnological application, and paves the way for future work to take advantage of chitinolytic activities. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12934-018-0895-x) contains supplementary material, which is available to authorized users.